THE EXPERIENCE OF CONVERGENT EDITORIAL STAFF FORMATION AT BELGOROD STATE UNIVERSITY - Veronika A. Smirnova (Высшее образование в России)
The article examines the functional capabilities of converged mass media in the modern information space and corporate media. The author considers the problems of the construction of convergent mass media edition, examines the impact of convergence in mass media and social processes on image positioning of the object in the modern information space.